PENGARUH MEDIA BIGBOOK TERHADAP KETERAMPILAN MEMBACA DAN MENULIS PERMULAAN SISWA SEKOLAH DASAR - Putri Rachmawati, Azmi; Gunawan, Dani; Nuriyanti, Risma (Pendidikan Guru Sekolah Dasar Institut Pendidikan Indonesia Garut, 2022)
The purpose of this study was to determine the effect of the use of Bigbook learning media on the ability to read and write at the beginning of grade II elementary school students. This research is a quasi-experimental research with Non-Equivalent Control Group Design. Based on the results of statistical data analysis, for the initial reading ability, the value of t count = 4.44 and t table = 1.68 can therefore be concluded that there is an influence from the use of bigbook media. Against students' initial reading ability. As for the initial writing ability, the value of t count = 2.96 and t table = 1.68 so that it can be concluded that there is an influence from the use of bigbook media on students' initial writing ability